KOMBINASI (MIXED-METHODS) DALAM PRAKTIS PENELITIAN ILMIAH - Faisal Hakim Nasution; Risnita; M. Syahran Jailani; Roni Junaidi (Jurnal Genta Mulia, 2024)
This paper aims to discuss the combination research model or what is known as mixed-methods. The intended meaning in research method is any planned, systematic, scientific, and rational activity in collecting facts. Meanwhile, the research in this paper focuses more on the approach taken in the combination research model (mixed-methods). In this research, the researcher deeply examines the concept and application of research approaches in various previous scientific studies. The materials studied are theoretical studies and results of previous research, both from national and international books and journals. The author employs data analysis with a descriptive qualitative approach. The research results indicate that the use of methods in scientific research has been able to reveal truths and new knowledge for the development of beneficial scientific knowledge for human life. The use of the combination research method (mixed-methods) encourages deeper, more comprehensive, and holistic problem-solving.